Postharvest physiology and biochemistry of Valencia orange after coatings with chitosan nanoparticles as edible for green mold protection under room storage conditions - Alshallash, Khalid S.; Sharaf, Mohamed; Abdel-Aziz, Hosny F.; Arif, Muhammad; Hamdy, Ashraf E.; Khalifa, Sobhy M.; Hassan, Mohamed F.; Abou ghazala, Mostafa M.; Bondok, Ahmed; Ibrahim, Mariam T. S.; Alharbi, Khadiga; Elkelish, Amr (Frontiers in Plant Science, 2022)
Because of their unique features, nanomaterials have been proposed and have gained acceptance in postharvest applications in fruit. Increasing the storage life and improving the quality of Valencia oranges was investigated using nano-chitosan. A chitosan nanoparticle was prepared by using high-energy ball milling. Chitosan nanoparticles were characterized by Dynamic light scattering, FTIR spectroscopy and Surface morphology by transmission electron microscopy. Fully mature Valencia oranges were harvested and then coated with one of these concentrations (0.2, 0.4, and 0.8% nano-chitosan) and control. The fruits were stored under room storage conditions for 75 days. The quality parameters (fruit weight losses, fruit decay percentage, fruit firmness, total acidity, total soluble solids percentage and T.S.S./acid ratio, ascorbic acid content) were taken in biweekly intervals after 0, 15, 30, 45, 60, and 75 days. Beside the in vitro testing of antifungal activity of chitosan nanoparticles. According to the findings of the two succeeding seasons, the nano-chitosan 0.8% treatment showed the best effects and had the lowest rate of fruit weight loss, fruit deterioration, and T.S.S./acid ratio in comparison to the other treatments in both seasons. Furthermore, the 0.8% nano-chitosan reveled the highest levels of fruit hardness and fruit pulp firmness. Fruit weight loss, fruit deterioration, TSS, and TSS/acid ratio, as well as other metrics, were steadily elevated prior to the storage time. The best results were obtained when Valencia oranges fruits were treated with 0.8% nano-chitosan for 75 days at room temperature.